2012
DOI: 10.1021/cm302227t
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Electron Transfer between Single-Walled Carbon Nanotubes and Diazonium Salts for High Purity Separation by Electronic Type

Abstract: Diazonium salts preferentially react with metallic single-walled carbon nanotubes (SWNT) over semiconducting SWNT, enabling the separation of SWNT by electronic type. Therefore, the reaction selectivity of diazonium salts for metallic SWNT is crucial for high purity separation of both metallic and semiconducting SWNT. Herein, we developed an efficient method of increasing the reaction selectivity by manipulating the redox potential of diazonium salts. The electron affinity of diazonium salts is effectively low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In a ground-breaking work, Strano et al 10 have shown that the covalent functionalization of surfactant-individualized, neutral SWCNTs with diazonium salts proceeds with a high selectivity towards metallic carbon nanotube species. On this basis, SWCNTs can be sorted by metallicity utilizing electrophoresis11 or density gradient methods 12,13. A fundamental prerequisite for this electronic type selective functionalization is a successful individualization of the neutral carbon nanotube species by application of highly efficient surfactant molecules and meanwhile, the reaction is well-understood and the mechanism has been elucidated 14,15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a ground-breaking work, Strano et al 10 have shown that the covalent functionalization of surfactant-individualized, neutral SWCNTs with diazonium salts proceeds with a high selectivity towards metallic carbon nanotube species. On this basis, SWCNTs can be sorted by metallicity utilizing electrophoresis11 or density gradient methods 12,13. A fundamental prerequisite for this electronic type selective functionalization is a successful individualization of the neutral carbon nanotube species by application of highly efficient surfactant molecules and meanwhile, the reaction is well-understood and the mechanism has been elucidated 14,15.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a higher density of states of SWCNTs in the vicinity of the singly occupied molecular orbital/lowest occupied molecular orbital (SOMO/LUMO) of the aryl diazonium radical/cation pair – i.e. higher charging density – directly leads to a more efficient electron charge transfer from the charged nanotubides to the adsorbed electrophilic trapping reagent 13. In addition, the calculations reveal no correlation of the PhN 2 radical/cation-SWCNTs interaction energy with varying tube diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a calibration utilizing Raman spectroscopy can employ for a very quick, but equally raw estimation of the DoF. When changing the type of diazonium salt (varying in reactivity due to electron‐withdrawing or ‐donating moieties) or the type of SWCNT starting material (varying in reactivity due to diameter, metallicity, inherent defects, and other factors), mentioned calibration procedure will most likely require modification. Whether this method can be adapted for the investigation of other nanomaterials such as graphene, MWCNTs, or non‐carbon‐based ones needs to be investigated in future works.…”
Section: Resultsmentioning
confidence: 99%
“…Among functionalization routes which often require very aggressive chemicals like elemental fluorine, carbenes, nitrenes, or alkali metals under strictly inert conditions, one of the rather simple, low‐hazardous, rapid, and non‐destructive pathways is the reaction between neutral SWCNTs and diazonium salts. The reaction is known since 2001 and the underlying single‐electron transfer (SET) mechanism has been studied well . Nevertheless, analytic methods utilized for nanomaterials like SWCNTs are limited mainly due to their polydispersibility, making classic techniques like nuclear magnetic resonance (NMR) and mass spectrometry (MS) unfavorable.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1(b) depicts a schematic diagram representing a process of surface functionalization of individual carbon nanotubes of the HACNT array with NH 2diazonium after the array synthesis and then subsequent RITC functionalization. The amine groups functionalized on the outer surface of carbon nanotubes are generally expected to act as an electron donor to give electrons towards the nanotube because of their relatively high reduction potential over the valence band of the semiconducting single-walled carbon nanotubes [20,21]. In addition, the NH 2 -diazonium functionalization on the nanotubes would allow mediation of a further functionalization of RITC on the NH 2 -diazonium functionalized nanotube assembly by replacing NH 2 -group with RITC, which exhibits fluorescence in the visible light wavelength regime [22].…”
Section: Resultsmentioning
confidence: 99%